Peningkatan keterampilan menghitung keliling bangun datar menggunakan teknik takalintar pada peserta didik kelas iii sekolah dasar - Wahyu Dasih Panuntun Utami; Siti Istiyati; Sri Marmoah (Universitas Sebelas Maret, 2019)
Abstract. The purpose of this research is to increase the skills of calculating the circumference of flat wake using takalintar technique in the 3rd grade of SD 2 Dodogan, Bantul 2018/2019 school year. This classroom action research is carried out in three cycles, each cycle consisting of two meetings with four stages, namely planning, action, observation, and reflection. The subjects of this study were teacher and 3rd grade students, amounting to 15 students. This study uses observational techniques, interviews, documentation, and tests. Data analysis using interactive data analysis with steps of data collection, data reduction, data presentation, and conclusions. The data validity test technique and technical triangulation The results on skills of calculating the circumference of flat wake increase from initial condition 56,1 (20%) to 75.0 (47%) in the first cycle, 80,0 (67%) in second cycle, and 88,9 (80%) in third cycles. Based on the results of this research, it was concluded that through the application of takalintar technique can increase the skills of calculating the circumference of flat wake in the 3rd grade of SD 2 Dodogan, Bantul 2018/2019 school year.Keywords : skills of calculating, the circumference of flat wake, takalintar technique, elementary school